Optimization of Processing Conditions and Enhancement of Quality and Storage Stability Of Clarified Sapodilla (Achras Zapota) Juice - Sin, Hwee Nee (2006)
This study was carried out to optimize conditions for hot water extraction (HWE) and enzymatic clarification in the production of clarified sapodilla juice. The effects of different level of fining treatment and storage condition on haze reduction of clarified sapodilla juice during storage were also investigated. The physico-chemical characteristics (physical measurement of fruits, total soluble solids, pH, titratable acidity, colour measurement, clarity and viscosity) of clarified sapodilla juice made from three fruit varieties were studied. The juice produced from the Subang variety possessed desirable lightness, clarity and viscosity and was therefore found to be suitable in the production of clarified sapodilla juice. The optimum conditions of hot water extraction (HWE) for production of sapodilla juice were determined using Response Surface Methodology (RSM). Time and temperature combinations in the range of 30-120 min and 30-90°C were the independent variables and their effects on juice yield, odour, taste and astringency were investigated. The results showed that extraction temperature was the most important factor that affected characteristics of the juice as it exerted a significant influence on all the dependent variables. Higher temperature increased juice yield, taste and odour but also showed an increased astringency, which affected the acceptability of the juice. The results implied that an optimum sapodilla juice extraction condition using HWE to be at 60°C for 120 min. The optimum conditions for enzymatic clarification of clarified sapodilla juice were also determined using RSM. Sapodilla juice was treated with pectinase enzyme at different incubation times (30-120 min), temperature (30-50ºC) and enzyme concentration (0.03-0.10%). These three factors were used as independent variables and their effects on turbidity, clarity, viscosity and colour (L values) of the juice were evaluated. Significant regression models describing the changes of turbidity, clarity, viscosity and colour (L values) with respect to the independent variables were established, with the coefficient of determination, R², greater than 0.8. The results indicated that enzyme concentration was the most important factor that affected characteristics of the juice as it exerted a significant influence on all the dependent variables. The recommended enzyme clarification condition was 0.1% enzyme concentration at 40ºC for 120 min. The clarified sapodilla juice was then subjected to different level of fining treatments namely bentonite at 0.25% (X), 0.10% (Y) and control (Z-without treatment) and stored at 4, 25 and 37°C. The effects of bentonite fining at different levels and storage temperature on haze reduction were monitored during 24 weeks of storage. Haze reduction was notable for samples stored at 4°C with 0.25% bentonite treatment (X) followed by samples stored at 4°C with 0.10% bentonite treatment (Y). Lower temperature slowed down the physical chemical changes that took place in juice and helped retain the quality and colour of juice during storage, while higher temperature induced and accelerated the physical chemical changes during storage. Fining treatment significantly reduced the turbidity and browning index of the juice during storage compared to samples without fining. The appropriate level of fining treatment was important in haze reduction where samples treated with 0.25% bentonite (X) showed greatly reduced haze formation followed by samples treated with 0.10% bentonite treatment (Y). All the samples passed the microbial test and were safe for consumption at the end of the storage period. Samples stored at 4°C with 0.25% bentonite treatment (X) possessed the highest overall acceptability scores after 24 weeks storage, while samples stored at 37°C without treatment (Z) showed the lowest overall acceptability.